2013
DOI: 10.5581/1516-8484.20130053
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to treatment with imatinib in chronic myeloid leukemia: a study of the first decade of responses obtained at a Brazilian hospital

Abstract: ObjectiveThe aim of this study was to identify the reasons for failure in adherence to imatinib mesylate treatment in chronic myeloid leukemia. MethodsA retrospective review was performed of 100 non-electronic records of patients with Ph+ chronic myeloid leukemia treated with imatinib mesylate. The study period was from January 2001 to January2011. Data were analyzed by Chi-Square and Correspondence analysis using the Statistical Analysis System software package. ResultsAt the beginning of treatment 41% of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The low response rate in our cohort may be due to the delay between diagnosis and treatment. Incomplete adherence to the treatment is also likely to have an impact on the low response rates we observed, as several studies demonstrate that the poor adherence to the treatment is associated with a lower response in CML [22][23][24].…”
Section: Discussionmentioning
confidence: 80%
“…The low response rate in our cohort may be due to the delay between diagnosis and treatment. Incomplete adherence to the treatment is also likely to have an impact on the low response rates we observed, as several studies demonstrate that the poor adherence to the treatment is associated with a lower response in CML [22][23][24].…”
Section: Discussionmentioning
confidence: 80%
“…Real-world studies of oral anticancer agents show that substantial numbers of patients (20-47%) are nonadherent, 14,15,29,30 mainly due to AEs, and a lack of understanding by patients of the importance of taking their medication as prescribed. [14][15][16]29,30 The FCS program addresses both of these issues by promoting a collaborative approach to AE education and management, and facilitating co-operation and teamwork between pharmacists, physicians, nurses, and patients themselves.…”
Section: Introductionmentioning
confidence: 99%
“…Among the 14 studies analyzed, seven referred only to adherence, one referred only to discontinuation, five assess adherence and discontinuation and one included only suboptimal adherers. It was evident that few studies have assessed the achievement of cytogenetic and molecular response, which are important parameters for analyzing the absence of Philadelphia chromosome, as well as reduced levels of BCL-ABL rearrangement (Marin et al, 2010;Cid et al, 2013;Reis et al, 2013). In addition, four studies showed adherence rates relatively low to imatinib, such as between 19.0 and 53.0%.…”
Section: Resultsmentioning
confidence: 99%